Forming Peace: Pedagogies and the Foundations of Peace Education at Faith-Based Universities in Indonesia - Geovasky, Imanuel; Christiani, Tabita Kartika; Sofjan, Dicky; Ahnaf, Mohammad Iqbal (Religió Jurnal Studi Agama-agama, 2026)
This article examines peace education at two faith-based universities in Yogyakarta, Indonesia, viz. UIN Sunan Kalijaga and Universitas Kristen Duta Wacana (UKDW), in the context of rising intolerance and radicalism amidst Yogyakarta’s image as an inclusive city. Using a qualitative approach, this study explores how historical context, theological foundations, and pedagogical models shape peace education practices at both institutions. This study collected primary data from semi-structured interviews with key informants from each university. Findings indicate that peace education is developed through distinct forms of theological negotiation. UIN Sunan Kalijaga emphasizes epistemological transformation from a normative-textual approach to a scientific-multidisciplinary framework through an integration-interconnection paradigm, while UKDW develops a holistic theology of peace that focuses on civil society reconciliation through experiential learning. The study concludes that the effectiveness of peace education at faith-based universities depends on the institution’s ability to interpret and contextualize religious teachings through interfaith dialogue. This article contributes by demonstrating that religious identity can serve as a pedagogical resource in promoting tolerance.